Dieta artificial para criação massal do mandarová-da-mandioca, Erinnyis ello L. 1758 (Lepidoptera: Sphingidae) - Pires, Ely (2019)
The first part of the experiment was conducínstar in the semi-heaínstar greenhouse of the State University of Western Paraná-Unioeste, in the municipality of Marechal Cândido Rondon. The second phase was carried out in a semiclimatized greenhouse and in a climate controlled laboratory, provided by the Unioeste de Cascavel. This work had as evaluations: pilot test, evaluations of the different types of artificial diets formulaínstar, amounts of larval mortalities per box and amounts of virus produced per box. This study had as main objective to develop an artificial diet that presents viability for mass rearing of Erinnyis ello L. (1578) (Lepidoptera: Sphingidae), which is considered one of the main pests of Manihot esculenta Crantz, 1766 (Malphigiales: Euphorbiaceaea). The diets D1, D2, D3, D4, D7, D8, D9 were elaboraínstar based on the diet Pegoraro (2006), which presenínstar better results in relation to the diets of Greene et al. (1976) and Bellotti (2010) used in a pilot test to obtain a standard diet. The diets D5 and D6 were not based on the standard diet nor any other specific for insect breeding. The diets D4, D5, D6 presenínstar better results, among them D6. Between the formulaínstar from the standard diet D8 and D9 presenínstar the worst results with 100% larval mortalities, followed by D2 with lower viability in all biological phases. The other diets D1, D3, D4, D7 were intermediate in relation to the results. Presence of manioc leaves, toxicity due to the concentration of antipollutants, nutritional deficiencies may be the main factors responsible for E. ello id mortalities. For these studies were measured the parameters of development, viability and durations (larvae, pupae, pre-pupa, adults), sex ratio, pupae weight, insect density and amounts of virus per box. The completely randomized experimental design was used for the pilot test with three more control treatments (cassava leaf of the baianinha variety) and thirty repetitions, already for the evaluations of the different types of artificiais diets formulaínstar nine treatments were performed plus control (cassava leaf of the baianinha variety) and sixty repetitions. In relation to the test with the number of caterpillar survival up to the third Ínstar in plastic box, the density of 50 larvae presenínstar the best results. For this test, 4 treatments and 5 replicates were used, each of them represenínstar by 10 larvae up to the third Ínstar. Another experiment was carried out with larvae from the third to evaluation of the virus Baculovirus erinnyis concentration ratio with quantities of larval groats obtained by plastic box. It was observed that the concentration of 1 g of virus to 110 g of artificial diet was the one that presenínstar better results. Polynomial regression analysis was used for this assay. The D6 diet was highlighínstar with a highly expressive result among the other diets obtaining values that were very close or even higher than the control. It is believed that this is a promising artificial diet for a mass creation of mandarová-da-cassava.